2020
DOI: 10.21203/rs.3.rs-117666/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct symptoms and underlying comorbidities with latitude and longitude in COVID-19: A systematic review and meta-analysis

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is straining global health resources and the prevalence of severe disease appears to vary across countries. In accordance with PRISMA guidelines, we performed a systematic review and meta-analysis of clinical features and underlying medical conditions of COVID-19. Eighty-seven studies, involving 1,434,931 COVID-19 patients from the Americas, Asia, Europe, and Oceania, were included. Geographically, the rate of severity was highest in Asia (95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Probiotics deserve more attention in regulating gut microbiota, maintaining intestinal homeostasis and serving as an antiviral mechanism. [162][163][164] Studies of probiotic therapy as postexposure prophylaxis for COVID-19 also suggest a potential protective effect. One study included 182 participants with close exposure to COVID-19; it included a follow-up for analysis of symptoms and the fecal microbiome after 28 days of continuous probiotic supplementation.…”
Section: Probiotics Alleviate Uncomfortable Symptoms Of Covid-19mentioning
confidence: 99%
“…Probiotics deserve more attention in regulating gut microbiota, maintaining intestinal homeostasis and serving as an antiviral mechanism. [162][163][164] Studies of probiotic therapy as postexposure prophylaxis for COVID-19 also suggest a potential protective effect. One study included 182 participants with close exposure to COVID-19; it included a follow-up for analysis of symptoms and the fecal microbiome after 28 days of continuous probiotic supplementation.…”
Section: Probiotics Alleviate Uncomfortable Symptoms Of Covid-19mentioning
confidence: 99%
“…The data was collected from 1382 designated COVID-19 screening centers in South Korea. These centers consist of national safe hospitals (263), dedicated respiratory clinics (518), (15). The process of initial screening, transfer, admission to a hospital or community treatment center (CTC) is presented in Fig.…”
Section: Data Source and Study Cohortmentioning
confidence: 99%
“…Previous studies revealed that the outbreaks of COVID-19 were associated with latitude, temperature, and humidity measurements, which reflects seasonal variation in the incidence of respiratory viruses [14,15]. Thus, geographic information of latitude and longitude have been integrated into our model.…”
Section: Data Collection and Measurementmentioning
confidence: 99%
“…An earlier version of this manuscript [ 49 ] has been presented as preprint in Research Square according to the following link: https://www.researchsquare.com/article/rs-117666/v1 .…”
Section: Disclosurementioning
confidence: 99%